Language-Paradox-Poetics - James J. Y. Liu (Princeton University Press, 2014)
The focus of this book is a kind of Chinese poetics that I name "the poetics of paradox" because it espouses the paradoxical view that in poetry, the less is said, the more is meant. Since this poetics originated from a paradoxical view of language seen in early Chinese texts, I deal first with the paradox of language. Instead of proceeding immediately to show how the paradoxical view of language led to the emergence of the poetics of paradox, I consider the nature of all poetics as a metaparadox in chapter 2, before presenting the poetics of paradox in chapter 3. In chapter 4, I discuss the implications of the poetics of paradox for interpretation and the paradoxical nature of interpretation itself. I further.sug: gest possible points of convergence between the iraditioaaL Chinese poetics of paradox and contemporary Western poetics and hermeneutics. Throughout the book I juxtapose Chinese and Western texts without regard for chronology. I do so not in an antihistorical or ahistorical spirit but for the following reasons. First, I am not concerned with claiming chronological priority for Chinese poetics, but with calling attention to a particular kind of Chinese poetics that is intrinsically interesting and that provides points of fruitful comparison with Western poetics. Second, I believe that only by means of juxtapositions of texts from Iwo ,different traditions-ean-we bring into relief what is truly distinctive in each tradition. Third, such juxtaposition will also enable us to become aware of the unspoken presuppositions about the nature of language, poetry, poetics, and interpretation that underlie each tradition, thus paving the way for; a^^iruinÂ£ly_coiriparati^4X)eJics,-freeirom both Eurocentnsm and Sinocenixisiri_